IMPACT OF EXCHANGE RATEON FOREIGN DIRECT INVESTMENT: EVIDENCE FROM UNILEVER IN NIGERIA - Uthman, Fatima Zahra (Kashere Journal of Management Sciences, 2025)
The study investigates the effect of exchange rate on foreign direct investment in Nigeria. The main objective of this study is to investigate the effect between exchange rate and Foreign Direct Investment. The set of the determinants of FDI can be very large but exchange rate is one of the profound determinants. Nonetheless, exchange rates have become extremely volatile due to its fragility to adapt to the changes in domestic and international financial markets. In this study, time series data have been used for exchange volatility and FDI 2014-2023 for Nigeria. After collection of data on above stated variables, different time series econometrics techniques (unit root test, volatility analysis, cointegration technique and causality analysis) have been applied for the purpose of analysis. The results squeezed from the study demonstrate that FDI is positively associated with Naira depreciation and exchange rate volatility deters FDI.